The challenge of nuclear-armed regional adversaries - Ochmanek, David A. (Rand Corp., 2008)
"North Korea's test of a nuclear weapon in 2006 shows that such weapons are within reach of determined regional powers. Thus, defense planners in the United States and elsewhere must begin now to confront the new security challenges posed by nuclear-armed regional adversaries. While U.S. conventional and nuclear forces will continue to have deterrent effects on the leaders of regional adversaries such as North Korea and Iran, the dynamics of the deterrent balance vis-à-vis these actors may be quite different from that to which the United States became accustomed during the Cold War. The weakness of these states at the conventional level, coupled with the high stakes they will have at risk in a conflict with the United States, could lead them to seriously consider brandishing or using nuclear weapons in a conflict. This, in turn, could compel U.S. leaders to temper their military and political objectives in such conflicts. To improve the United States' military and political leverage in these situations, a great deal more needs to be done to develop and field capabilities, such as multilayered theater missile defenses and improved surveillance and target-tracking capabilities, that can prevent the enemy's use of nuclear weapons."--Publisher's website.